Wiara w porządku ratio - Bańka, Aleksander R. (Studia Pastoralne, 2026)
When in 1977, in a book entitled At the root of modern atheism, French philosopher Marcel Neusch formulated the thesis about the coming of postatheistc age, he probably did not think, that at the beginning of the twenty-first century, atheistic thought reborn in the form of a so-called „new atheism”. Its main representatives: Richard Dawkins, Christopher Hitchens, Daniel C. Dennett and Sam Harris, taking the position of scientific scientism, attack with a renewed vigor not only all forms of religion, but also skepticism, relativism and epistemological agnosticism. Their main efforts focus on trying to argue that all faith is an act completely irrational, and the non-existence of God can be confirmed by scientific methods. This article is a polemic with the main theses of the new atheists. It shows the actual place of faith in the order of ratio and discusses the problem of possibility of proving the existence or the non-existence of God.